HUBUNGAN TINGKAT KREATIVITAS MENGAJAR GURU DENGAN PRESTASI BELAJAR PADA SEKOLAH DASAR NEGERI SINDANG BARANG - heru Achmad Maulana; Omon Abdurakhman (AL - KAFF: JURNAL SOSIAL HUMANIORA, 2018)
Teachers' lack of creativity in the learning process can to than optimal learning process, so that the material presented be uncompleted. Given the existence of these, the role of teachers is one of the factors that have the responsibility for the intellectual life of students. Personal decency is expected ably present in each of the students. Therefore, teachers should be responsible for all the attitudes, behaviors and actions in order to foster the spirit and character of the students. Thus, the teacher's responsibility is to form students to become proficient morals of people, useful for religion, homeland, nation in the future. The teacher's responsibility more important is to be able to follow all the progress of Science and Technology (Science and Technology) today. Obtained information that the creativity of teachers to teach in elementary school Sindangbarang 3 Bogor City there are still some problems, namely: 1) Teachers tend to lack the ability to issue new ideas; 2) Teachers in learning activities tend to take on the subject matter alone of the teacher without asking questions about subjects that are not understood students, and 3) The learning process is executed teachers tend to be monotonous. The purpose of this research was to determine the correlation between teachers' teaching creativity and academic achievement in SDN 3 Sindang Barang Bogor City. The sample in this study is a Grade 5 student at SD Negeri 3 Bogor City Sindangbarang totaling 30 people. The final result of this study shows there is a relationship between the level of creativity of teaching teachers and academic achievement in elementary school Sindangbarang 3 City Bogoryang produce rxy of 0,550 and when consulted with a table of values criticism "r" with a significance level of 5% obtained a value of 0.361. Thus r count> r table (0.550> 0.361). Obtained t count> t table (2.623> 2.048) then from these results it can be said that the relationship variables X and Y are significant. Contribution of variable X to variable Y amounted to 30.25% and the remaining 69.75% influenced by other factors.